1996
DOI: 10.1055/s-2007-1005437
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Features of Metastatic Tumors in the Upper Gastrointestinal Tract

Abstract: Panendoscopy with histological examination is a way of identifying metastatic tumors to the upper gastrointestinal tract when patients have a known primary cancer and symptoms relating to the upper gastrointestinal tract. However, there is no specific information allowing the origin of a lesion to be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 0 publications
1
52
0
8
Order By: Relevance
“…Lung and breast neoplasias were the most common primary sites of gastric metastases in several series [2][3][4][5][10][11][12], and these findings reflect the high incidence of these tumors among the general population [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung and breast neoplasias were the most common primary sites of gastric metastases in several series [2][3][4][5][10][11][12], and these findings reflect the high incidence of these tumors among the general population [13].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of metastasis in the stomach is a rare condition [1][2][3] and the main studies reported in the literature are based on endoscopic findings [4][5][6], tube was divided into three equal parts, for the purpose of locating the metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Nodules, solitary or multiple, sometimes ulcerated polypoid submucosal masses, as well as infiltrating constricting tumors have also been described (25)(26)(27)(28). The most frequent locations of gastric metastases are reported to be the middle or upper third of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11 On the other hand, the most prevalent primary sites of metastasis to the stomach are the lung, breast, skin (melanoma), and esophagus. Lung and breast neoplasia were the most common primary sites of gastric metastases in several series, 9,[12][13][14] and these findings reflect the high incidence of these tumors among the general population. Corroborating the data from other authors, the clinical symptom most frequently requiring an EGD in this series, was upper gastrointestinal bleeding.…”
Section: Fig 5 Esophagogastroduodenoscopy Finding After Chemothrerapymentioning
confidence: 99%
“…Corroborating the data from other authors, the clinical symptom most frequently requiring an EGD in this series, was upper gastrointestinal bleeding. [12][13][14] Within the subgroup of patients with cancer of the esophagus, the symptoms justifying EGD were dysphagia and chest pain. Unfortunately, the diagnosis of metastasis in the symptomatic phase signifies a late diagnosis, at a stage which renders any treatment procedure ineffective.…”
Section: Fig 5 Esophagogastroduodenoscopy Finding After Chemothrerapymentioning
confidence: 99%